Adherence, tolerability, and outcome after 36 months of isoniazid-preventive therapy in 2 rural clinics of Swaziland: A prospective observational feasibility study. Issue 35 (September 2017) - Mueller, Yolanda; Mpala, Qhubekani; Kerschberger, Bernhard; Rusch, Barbara; Mchunu, Gugu; Mazibuko, Sikhathele; Bonnet, Maryline
Abstract : Abstract: Although efficacy of 36 months isoniazid preventive therapy (IPT) among HIV-positive individuals has been proven in trial settings, outcome, tolerance, and adherence have rarely been evaluated in real-life settings. This is a prospective observational cohort study conducted in 2 primary care rural clinics in Swaziland. After negative tuberculosis symptom screening, patients either with the positive tuberculin skin test (TST) or after tuberculosis treatment were initiated on IPT for 144 weeks. In addition to routine clinic visits, adherence was assessed every semester. Of 288 eligible patients, 2 patients never started IPT (1 refusal, 1 contraindication), and 253 (87.8%), 234 (81.3%), and 228 (79.2%) were still on IPT after 48, 96, and 144 weeks, respectively (chi 2 P = .01). Of 41 patients who interrupted IPT before 144 weeks, 21 defaulted (of which 17 also defaulted HIV care); 16 stopped because of adverse drug reactions; 2 were discontinued by clinicians' mistake and 1 because of TB symptoms. Five patients (1.7%) died of causes not related to IPT, 5 (1.7%) developed TB of which 2 were isoniazid-resistant, and 9 (3.1%) were transferred to another clinic. As an indicator of adherence, isoniazid could be detected in the urine during 86.3% (302/350) and 73.6% (248/337) of patient visits in the 2 clinics, respectively (chi 2 P < .001). The routine implementation of IPT 36 months was feasible and good patient outcomes were achieved, with low TB incidence, good tolerance, and sustained adherence.